2014
DOI: 10.1128/jvi.02686-13
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Emergence and Establishment of a Newly Dominant Genotype of Japanese Encephalitis Virus throughout Asia

Abstract: In recent years, genotype I (GI) of Japanese encephalitis virus (JEV) has displaced genotype III (GIII) as the dominant virus genotype throughout Asia. In this study, the largest collection of GIII and GI envelope gene-derived viral sequences assembled to date was used to reconstruct the spatiotemporal chronology of genotype displacement throughout Asia and to determine the evolutionary and epidemiological dynamics underlying this significant event. GI consists of two clades, GI-a and GI-b, with the latter bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
150
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 39 publications
6
150
2
Order By: Relevance
“…Alternatively, stochastic events leading to a genetic bottleneck event within or among hosts may also lead to the emergence of new genetic variants that could compete with existing viral populations and may ultimately form new genetic clades. Such replacement events are not unique to DENV and have also been reported for other flaviviruses, such as Japanese encephalitis and West Nile viruses (25)(26)(27).…”
mentioning
confidence: 60%
“…Alternatively, stochastic events leading to a genetic bottleneck event within or among hosts may also lead to the emergence of new genetic variants that could compete with existing viral populations and may ultimately form new genetic clades. Such replacement events are not unique to DENV and have also been reported for other flaviviruses, such as Japanese encephalitis and West Nile viruses (25)(26)(27).…”
mentioning
confidence: 60%
“…The Indonesian/Malaysian region is thought to be the origin of all genotypes of JEV (Solomon et al, 2003), and in several South-east Asian countries, GI was isolated as a minor JEV strain before the 1990s. Comprehensive phylogenetic analysis of the GI JEV strains has demonstrated that the old and the new GI strains form distinct lineages (Gao et al, 2013;Schuh et al, 2014), suggesting that genetic differences in the new GI genome might be responsible for the spread of GI viruses. Recent findings indicate that GI JEV exhibits a higher replicative ability in mosquitoes than GIII JEV (Schuh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study of E protein gene sequences revealed that genotype I could be subdivided into two clades, GI-a and GI-b, with the majority of isolates placed in GI-b. Furthermore, viral multiplication and temperature sensitivity analyses revealed that the GI-b isolate had significantly higher infectivity titers in mosquito cells from 24 to 48 h postinfection, providing new insight into how GI emerged as the dominant lineage (23). Nevertheless, the recent publication of a large number of whole-genome sequences of JEV and the availability of a very large number of sequences from other genes make further examination of the GIII-to-GI displacement event worthwhile.…”
mentioning
confidence: 99%